The Importance Of Improving The Legal Culture Of The Individual In The System Of Social Relations Of Society - Abror Idibоev (Global Scientific Publishing, 2024)
The article discusses the issues of the importance of the level of legal culture of a person in the development of social relations in society. It also scientifically analyzes the role of our citizens' deep knowledge of the legal foundations of all spheres of society in ensuring social stability.
Keywords: Society; social relations; spiritual life